Gap-coupled microstrip array antenna for wide-band operation - Meshram M.K.; Vishvakarma B.R. (My University, 2025)
The theoretical and experimental investigations carried out on a gap-coupled microstrip array antenna reveal that there is a significant improvement in VSWR and bandwidth characteristics of the gap-coupled microstrip array antenna as compared with a conventional microstrip array antenna. The input impedance and the resonant frequency of the gap-coupled patch are found to depend heavily on the gap length as well as on the dielectric constant of the substrate material.